Deferred Tax Positions under the prism of financial crisis and the effects of a corporate tax reform - Evangelos Chytis; Evangelos Koumanakos; Costas Siriopoulos (University of Macedonia; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
The effects of corporate tax reforms in reported profits and firms' financial position have been extensively studied in the literature. However, only few studies disaggregate deferred tax items to jointly explore political implications and aspects of corporate behavior around such reforms. Greece's recent financial crisis and economic recession provides an intriguing setting for examining possible incentives and consequences of substantial tax rate changes, such as the 6% increase imposed by the Greek Government early in year 2013. Results reveal a totally different picture between financial and non-financial firms, with the former being clearly favored, at least from this short-run effect. More specifically, Greek banks, given the very significant Deferred Tax Assets Positions arising from the “haircut” of Greek Government Bonds known as PSI, strengthen their assets and net income by 1.58 billion Euros, corresponding to more than of their total losses at the end of 2012, whereas industrial firms experience a significant increase in long-term liabilities and a decrease in net income of 193%. These findings seem to coincide with the view that tax policy design is usually shaped by taking into consideration powerful groups' interests, as it normally happens with banks especially in periods of fiscal instability.
Conference: 12th Annual Conference of the Hellenic Finance and Accounting Association (H.F.A.A.), 13-14 December 2013, University of Macedonia, Thessaloniki , Greece
Keywords: M41; H25; 330; International Financial Reporting Standards; deferred tax; book-tax differences; tax policy